The Effect of Electric Current On Hydrogen Gas Production Using Water Electrolysis Process - Wardhana, Asepta Surya; Yuliatin, Umi; Yasmin, Amida (Jurnal Polimesin, 2024)
New renewable energy sources are being developed to replace conventional energy sources such as biofuels, electric cars, and solar cars in the transportation sector. However, this generation has limitations in that it requires external energy sources to be converted into electricity.This study examined the development of alternative energy sources through water electrolysis to produce hydrogen. The factors affecting the electrolysis process, such as the catalysts and external voltage, were investigated. The study successfully implemented hydrogen production using a wet cell electrolysis reactor design involving components such as an Arduino, MQ-8 gas sensor, and DS18B20 temperature sensor. This study used a reactor with electrodes of six plates, where the electrode plates werethe anode and cathode of three plates each. Hydrogen levels were measured using an MQ-8 semiconductor sensor. The test results showed that varying the current in the electrolysis reactor increased the hydrogen concentration to a maximum of 3405.77 PPM. A decrease in hydrogen levels occurred after 20-40 minutes due to the saturated electrolytes. Factors such as the ion concentration, hydration, ion attraction, and temperature also influence the conductivity of the solution duringelectrolysis. The results of this study obtained a minimum average hydrogen content of 646.054 PPM and a maximum of 2932.306 PPM. The reactor temperature conditions were stable at an average temperature of 27°C.